C4 economic for business : (Elsevier, 2005)
Brush up on difficult subject areas and gain invaluable question practice with CIMA Inter@ctive Study Systems. These CDROMs are the ideal way to supplement paper or classroom based learning of the Foundation subjects. CIMA Inter@ctive Study Systems each provide extensive syllabus coverage through the 60 hours of learning. Extensive question practice supplies important feedback on incorrect answers to allow you to quickly identify and fill gaps in your knowledge. Computer-based assessment is now the preferred method of examination, so computer-based learning is the best way to supplement your study and improve your chance of success.